The Evaluation of a Lateral Flow Strip Based on the Covalently Fixed End-On Orientation of an Antibody for Listeria monocytogenes Detection - Patsara Thongmee; Sawinee Ngernpimai; Oranee Srichaiyapol; Urairat Mongmonsin; Saowapak Teerasong; Nicha Charoensri; Molin Wongwattanakul; Aroonlug Lulitanond; Waewta Kuwatjanakul; Lumyai Wonglakorn; Rinjong Promsorn Kendal; Apiwat Chompoosor; et al. (My University, 2024)
In this study, the covalently fixed "end-on" orientation of a monoclonal Listeria monocytogenes antibody (mAb-Lis) to amino terminated oligo (ethylene glycol)-capped gold nanoparticles (NH2-TEG-AuNPs) was used to fabricate an in-house lateral flow strip (LFS), namely, the fixed "end-on" Lis-mAb-NH-TEG-AuNPs LFS. The aim was to evaluate the performance of the fixed "end-on" Lis-mAb-NH-TEG-AuNPs LFS in detecting L. monocytogenes. The proposed LFS enabled the sensitive detection of L. monocytogenes in 15 min with a visual limit of detection of 102 CFU/mL. Quantitative analysis indicated an LOD at 10 CFU/mL. The fixed "end-on" Lis-mAb-NH-TEG-AuNPs LFS showed no cross-reactivity with other pathogenic bacteria and practical performance across different food matrices, including human blood, milk, and mushroom samples. Furthermore, the clinical performance of the fixed "end-on" Lis-mAb-NH-TEG-AuNPs LFS for detecting L. monocytogenes was evaluated by using 12 clinical samples validated by the hemoculture method. It demonstrated excellent concordance with the reference methods, with no false-positive or false-negative results observed. Therefore, the fixed "end-on" Lis-mAb-NH-TEG-AuNPs LFS serves as a promising candidate for a point-of-care test (POCT), enabling the rapid, precise, and highly sensitive detection of L. monocytogenes in clinical samples and contaminated food.
Keywords: Biosensors and Analytical Detection